Kresťanské hagiografie (Život Márie Egyptskej, Život Margity/Mariny Antiochijskej) a texty tzv. jarného vynášania smrti (Moreny, Mařeny, Marzany) u západných Slovanov. Pokus o paralelné čítanie Christian Hagiographies (The Life of Mary of Egypt, the Life of Marjeta/Marina of Antioch) and Texts on the So-Called Spring Taking Away the Death (Morena) among West Slavs. An Attempt at Parallel Reading - Golema, Martin (Studia mythologica Slavica, 2009)
<span style="line-height: 115%; font-family: ’Calibri’,’sans-serif’; font-size: 11pt; mso-ansi-language: EN-US; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: ’Times New Roman’; mso-bidi-theme-font: minor-bidi; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The study builds on research and interpretation of texts of the so called “death (Morena, Mařena, Marzana) carrying-out in spring” among the western Slavs. The author tries to examine an assumption about the existence of a “chemically almost pure” Slavonic mythology goddess embodying death in texts about death carrying-out in spring. He tries to prove that it is a hybrid text unit originating in several text traditions, both in the identified Christian (Byzantine) text store and in early Slavonic myths.